Tretinoin in acne: retin-A. Issue 13 (22nd June 1973) - Unknown
Abstract : The development of acne is usually associated with increased sebum production (seborrhoea) and obstruction of the pilo-sebaceous duct. One result of this obstruction is bacterial colonisation of the glands and ducts; bacterial decomposition of sebum produces irritant substances, perhaps fatty acids, and eventually the gland ruptures liberating the sebum into the dermis, producing the inflammatory response which is a feature of acne. At present there is no satisfactory way of reducing sebum production. The bacteriological and biochemical changes secondary to obstruction can be modified with long-term use of an oral tetracycline, 250 mg once or twice daily for three months or longer. Attempts to influence the obstruction problem often succeed only partially. Such attempts include the use of ultraviolet radiation, sulphur, resorcinol (Acnil - Fisons; Eskamel - SKF), Brasivol (Stiefel), benzoyl peroxide (Benoxyl - Stiefel), Quinoderm (Quinoderm Co.), and removing blackheads mechanically. However some safe topical therapy is needed which will effectively banish blackheads, whiteheads and papules, especially in those patients whose acne is not adequately controlled by the traditional peeling agents. After large oral doses of vitamin A were found effective in acne vulgaris, 1 it was tried topically, and recently vitamin A acid, tretinoin, has been introduced as Retin-A (Ortho). This is an alcoholic solution containing 0.025% tretinoin.